Imidazole-based Derivatives as Potential Anti-platelet Inhibitors: DFT and Molecular Docking Study - I. K. Momin, Mehbub; A. Koorbanally, Neil; Honarparvar, Bahareh (Letters in Drug Design & Discovery, 2016)
Selected synthesized biologically active fluorinated diethyl-2-(benzylthio)-2,3-dihydro- 1H-imidazole-4,5-dicarboxylate derivatives exhibited promising anti-platelet aggregation activity against thrombin. With a view to understanding their structural features, some common electronic structural characteristics, including polarizability (α), ΔELUMO-HOMO, chemical hardness (η) and softness (S) were calculated using density functional theory (DFT) with B3LYP functional and 6-31+G* basis set. The high polarizabilities (α=139.554 A3, 138.459 A3) with low ΔELUMO-HOMO (3.761 eV,3.662 eV), low chemical hardness (η= 1.880 eV, 1.831 eV) and high chemical values of softness (S=0.265 eV, 0.273 eV) are observed for the two most active imidazole-based anti-platelet derivatives with reasonably good IC50 values (0.40 mg mL-1, 0.44 mg mL-1). Moreover, molecular docking analysis of these anti-platelet compounds in the active binding site of the thrombin receptor identified the potential interaction between these inhibitors with the active residues of thrombin. Inspection of the docked structures implies that the antiplatelet inhibition of the most active compounds is mainly due to the possibilities of hydrogen bonding interaction and intramolecular close contacts of some active residues of the thrombin receptor (Gly219, Glu192, Gly216, Trp60, Tyr60A, Trp215, Leu99, His57, Cys191, Lys60, Glu217) with anti-platelet leads. These results suggest that the active imidazole derivatives could be promising chemical scaffolds to target the thrombin receptor.
Keywords: Anti-platelet derivatives